Diseño Técnico y Construcción de una Máquina para Retirar la Estopa del Coco - Zapata Grisales, Rodrigo (Universidad Antonio Nariño, 2023)
The purpose of this project is the construction of a machine that allows to separate the tow from the coconut from the hard part of it, trying to minimize the factors risk of accident when performing this operation manually with short pointed tools, thus obtaining, a safer process for the operators and at the same time, a increase in the productivity of raw material processed.